Subcutaneous sarcoidosis: a report of 13 cases and its association with extracutaneous sarcoidosis - Yamamoto, Toshiyuki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
None, because this is submitted for Letter section.